Incidence and Severity of African Cassava Mosaic in Mubugu and Kalima Fields in Kalehe Territory, Eastern Democratic Republic of Congo - Ushindi Zihindula Victor; Deborah Mutarushwa (Research and Social Study Institute, 2026)
Background: Since cassava is a staple crop whose roots and leaves serve as a staple food in the Democratic Republic of the Congo in general and in Kalehe in particular, efforts to increase its productivity face numerous constraints, among which diseases, particularly the endemic form of mosaic disease, play a significant role.Aims: This study aimed to assess the incidence and severity of African cassava mosaic (ACM) disease in two clusters within the Kalehe territory in order to propose potential solutions to limit its spread and proliferation.Methods: To achieve this, surveys were conducted in 200 cassava fields. Two techniques, specifically analysis of variance and correlation analysis using Stata software, enabled us to interpret the field data.Results: The research results showed that the level of attack by African cassava mosaic virus on cassava was high in the Kalehe territory. ACM was present in both groups. The highest incidence of ACM was 56.39% in KALIMA and 56.030% in MUBUGU. By locality, the highest incidence of ACM was 57.3% in MAFUO, MAKUTA (56.3%), and KASHEWE (56.8%), followed by MAKWE (55.99%), MUSHUNGUTI (55.99%), LUKANDO (55.99%), KABARE (55.9%), MISIMA (55.99%), CIGOMA (55. 8%), and IRANGI (55.8%), with an overall average for these 10 localities of 56.21%. In addition, all the varieties identified in the fields at Kalehe, notably NAMALE, NAMBIYO, ELONA, and SAWASAWA, were susceptible to African cassava mosaic, with relative incidences of 73.5%, 72.26%, 38.99%, and 39.06%, respectively, and a high severity level ranging from 2 to 3. There was a negative relationship between mosaic severity and variety, i.e., the lower the level of mosaic severity, the less diseased the varieties. Hence, this study highlights local varieties, even though research regularly develops and disseminates improved varieties resistant to African cassava mosaic.Conclusion: African cassava mosaic disease showed a high incidence and severity across cassava fields in the Kalehe territory, indicating that the disease is widely distributed in the study area. All identified local cassava varieties were susceptible to the disease, highlighting the need for resistant varieties and improved disease management strategies.